Velocity at maximal oxygen uptake best predicts 3 km race time in collegiate distance runners - McCormack, W. P.; Shoepe, T. C.; Almstedt, H. C.; Jennings, C. A.; Capel, L. M. (Journal of Human Sport & Exercise, 2018)
Purpose: There is a lack of scientific investigation into the predictors of 3 km race performance in collegiate distance runners. The purpose of this investigation was to determine what physiological variables best predict 3 km race time in a group of collegiate distance runners. Methods: Twenty-one endurance trained runners (11 men, 10 women) volunteered for this investigation. Running economy (RE) and maximal oxygen uptake (VO2max) testing were conducted within 9 ± 6 days of the race in a single session. All participants ran in a 3 km race at an NCAA sanctioned track meet. Pearson`s product moment correlations were performed between 3 km race time and velocity at VO2max (vVO2max), relative VO2max, RE at 9.7, 11.3, 12.9, and 14.5 km•hr-1 and percent of VO2max. A stepwise multiple regression was performed with 3 km race time as the dependent variable and independent variables of vVO2max, VO2max, RE9.7, RE11.3, RE12.9, RE14.5. Results: The results revealed that vVO2max was the best predictor of 3 km race performance in a heterogeneous group of collegiate distance runners (R2=0.90). For the men, vVO2max remained the best predictor of 3 km race performance (R2=0.49). For the women, the best predictors of 3 km performance were vVO2max and VO2max (R2=0.97). Conclusions: Distance coaches should consider emphasizing vVO2max as a primary factor in training to improve 3 km race performance and conversely, the pace achieved in a 3-km race is a good predictor of vVO2max.